Development of a Prognostic AI-Monitor for Metastatic Urothelial Cancer Patients Receiving Immunotherapy - Trebeschi, Stefano; Bodalal, Zuhir; van Dijk, Nick; Boellaard, Thierry N.; Apfaltrer, Paul; Tareco Bucho, Teresa M.; Nguyen-Kim, Thi Dan Linh; van der Heijden, Michiel S.; Aerts, Hugo J. W. L.; Beets-Tan, Regina G. H. (Frontiers in Oncology, 2021)
Background. Immune checkpoint inhibitor efficacy in advanced cancer patients remains difficult to predict. Imaging is the only technique available that can non-invasively provide whole body information of a patient’s response to treatment. We hypothesize that quantitative whole-body prognostic information can be extracted by leveraging artificial intelligence (AI) for treatment monitoring, superior and complementary to the current response evaluation methods. Methods. To test this, a cohort of 74 stage-IV urothelial cancer patients (37 in the discovery set, 37 in the independent test, 1087 CTs), who received anti-PD1 or anti-PDL1 were retrospectively collected. We designed an AI system (named prognostic AI-monitor (PAM)) able to identify morphological changes in chest and abdominal CT scans acquired during follow-up, and link them to survival. Results. Our findings showed significant performance of PAM in the independent test set to predict 1-year overall survival from the date of image acquisition, with an average area under the curve (AUC) of 0.73 (p<0.001) for abdominal imaging, and 0.67 AUC (p<0.001) for chest imaging. Subanalysis revealed higher accuracy of abdominal imaging around and in the first 6 months of treatment, reaching an AUC of 0.82 (p<0.001). Similar accuracy was found by chest imaging, 5 to 11 months after start of treatment. Univariate comparison with current monitoring methods (laboratory results and radiological assessments) revealed higher or similar prognostic performance. In multivariate analysis, PAM remained significant against all other methods (p<0.001), suggesting its complementary value in current clinical settings. Conclusions. Our study demonstrates that a comprehensive AI-based method such as PAM, can provide prognostic information in advanced urothelial cancer patients receiving immunotherapy, leveraging morphological changes not only in tumour lesions, but also tumour spread, and side-effects lesions. Further investigations should focus beyond anatomical imaging. Prospective studies are warranted to test and validate our findings.